LOCAL WISDOM OF MUJAHADAH PRAYER AND ITS INFLUENCE ON TEACHER SPIRITUALITY IN EDUCATING AT PONDOK TAHFIDZ MAMBAUL ULUM WARU SIDOARJO - Alindra, Bagus Malik; Soebahar, Halim; Chotib, Moch.; Harisudin, Muhammad Noor (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
This study aims to explore the activity of Sholat Mujahadah as local wisdom towards teacher spirituality in educating students at the Mambaul Ulum Islamic Boarding School. The Mambaul Ulum Islamic Boarding School, which is an Islamic boarding school based on the Koran, has interesting habits carried out by its educators. This habit is transformed into a form of worship which they call the mujahadah routineThe Mujahadah tradition carried out at the Mambaul Ulum Islamic Boarding School is a manifestation of spiritual worship that not only strengthens the relationship between teachers and God but also functions as an effort to form the character of students. This study uses a qualitative approach with a case study method. Data collection techniques are done through observation, interviews, and documentation, while data analysis uses the Miles and Huberman model. The results of the study indicate that Sholat Mujahadah has a significant influence on teacher spirituality. This tradition helps teachers develop calmness, patience, and sincerity in educating students, improving the quality of teaching. This local wisdom not only functions as a religious ritual, but also strengthens social ties and spiritual values ​​in the Islamic boarding school environment.